RELATIONSHIP OF NON STRUCTURAL ANTIGEN 1 (NS1) EXAMINATION RESULTS TO CLINICAL SIGNS ,SYMPTOMS AND ROUTINE BLOOD EXAMINATION IN PATIENTS SUSPECTED DENGUE INFECTIONS AT INPATIENTS CLINIC OF VITA MEDIKA KEPUNG KEDIRI DISTRICTS - Charisma, Acivrida Mega (Indonesian Journal of Tropical and Infectious Disease, 2020)
Early diagnosis of dengue infection is important because late diagnostic can be fatal to the patient, remembered the journey of the disease is very rapid. Currently there has been developed an examination of a non structural 1 dengue antigen (NS1) that can detect dengue viral infections earlier, even on the first day of fever. However, not all health care centers have adequate laboratory facilities for NS1 checks.Clinical symptoms and signs as well as a routine blood test are indicators that become the basis of diagnosis in health care facilities with limited facilities. This study aims to determine the relationship of NS1 examination result to clinical symptoms and signs as well as the result of routine blood tests in patients suspected dengue infection. This research uses observational analytic method with cross sectional approach. The research was conducted in clinic laboratory and inpatient clinic room of Vita Medika Kepung Kediri from November 2017 to February 2018.The number of research samples of 30 people was determined by the consecutive sampling technique. NS1 examination was done by using rapid immunochromatography test method with mono kits. Routine blood examination was done by using Micros 60. Chi square test on relationship between clinical sign and symptoms  examination of dengue with the results of NS1 examination obtained p= 0,310 (p > 0,005), while the results of chi square test on the relationship of routine blood examination results haemoglobine levels, amount of leucocyte, platelet count and hematocite of NS1 examination result obtained p value in a row p = 0,235 (p > 0,05) , p = 0,013(p < 0,05) , p = 0,028(p < 0,05)  dan p = 0,132 (p > 0,05). There was a significant correlation between leucocyte count and platelet count to NS1 antigen exanimation result , but there was no correlation between clinical signs and symptoms of dengue patients, haemoglobine level and haematocryt value on NS1 antigen examination result.